Maurice Halbwachs: Classical Sociology after the Classics - Migliorati, Lorenzo (Italian Sociological Review, 2015)
The paper sets out to analyse the scientific production of Maurice Halbwachs (1877-1945). If in France he is substantially considered a classic to study, to publish and to republish, in other countries – in Europe, as in the United States – he is considered a lesser author, an epigone of Durkheim, though he was never even a direct alumnus of the latter. To me it seems, instead, that there is more than one reason why sociology should rediscover this figure, regarding both the theoretical aspect and that of empirical research. First. Halbwachs is rightly known for his studies on collective memory; and, in effect, these are pioneering and courageous works that have involved enormous gains for the sociological discipline in epistemological terms. Nevertheless, he is unjustly little known as concerns the many other themes that he dealt with. Second. Halbwachs’ sociological posture starts from Durkheimian organicism, but never slavishly bows to it. In this sense, it seems me that the true hidden pearl of this author lies in his conception of social reality as of a dialectical and constant tension between society and individual.